Selective decontamination of the digestive tract in esophagectomy and the incidence of pneumonia and anastomotic leakage: A systematic review and meta-analysis. - Sander Du X Oei; Jasper Gerrit Jan Verbruggen; Sanne Elisabeth Hoeks; Marcus Paulus Buise (PLoS ONE)
Background Despite advances in surgery, esophagectomy remains a major operation in which pneumonia and anastomotic leakage are causes of morbidity. It is currently unknown whether selective decontamination of the digestive tract (SDD) affects the incidence of postoperative pneumonia and anastomotic leakage in patients undergoing esophagectomy. The aim of this systematic review and meta-analysis is to summarize current evidence regarding SDD in patients undergoing esophagectomy. Methods We performed a comprehensive search in Medline, Web of Science, Embase, Cochrane Library and Google Scholar with articles included until August 2024. We included observational studies and clinical trials which were scored using the Cochrane Risk of Bias tool and The Risk Of Bias In Non-randomized Studies - of Interventions. A fixed effects model was used to pool results of the former studies. Results A total of five studies were identified with a total of 924 patients. All studies were assessed as either having serious bias or a high risk of bias. SDD usage was associated with a significantly lower incidence of pneumonia (OR 0.41; 95% CI 0.29 to 0.58; p < 0.00001; I2 = 26%; n = 924) and anastomotic leakage (OR 0.48; 95% CI 0.30 to 0.74; p = 0.001; I2 = 0%; n = 810). Pooled analysis regarding mortality, duration of hospitalization and duration of Intensive Care Unit stay could not be performed due to heterogeneous data, 4 of 5 studies reported lower mortality rates in patients receiving SDD. Conclusion Although the data indicates that using SDD in patients undergoing an esophagectomy was associated with a lower incidence of postoperative pneumonia and anastomotic leakage, the available studies were not of sufficient quality to make a recommendation, given their age and risk of bias. A high-quality randomized controlled trial using standardized outcome definitions is needed to substantiate claims about SDD use in esophagectomy.